Perception of Combined Method of Teaching on Learning among Student Nurses in Ebonyi State Nigeria: Lecture and Facilitation Methods. - Juliet, Ikwor Oyiri; E, Makata Ngozi.; C, Odikpo Linda; F, Ndubuisi Sunday; Beatrice, Obende Eyito; N., Uzoegbo Helen (International Journal of Nursing Education)
Introduction: Exploration of innovative teaching and learning methods to ascertain the modest means of imparting knowledge with the aim of producing ambidextrous students is ongoing; this study aims to determine the perception of the combined method of teaching on learning among student nurses in Ebonyi State, Nigeria: lecture and facilitation methods. Method: Mixed design (survey and quasi-experimental research designs) was adopted. A purposive sampling technique was employed to collect data from 242 student nurses in Ebonyi State. A researchers-developed questionnaire was used for data collection while collated data were analysed and presented in percentages, means, standard deviations, and t-tests. Result: The pre-intervention test was below average (25.5%), and the respondents perceive the combined lecture-facilitation method as not very effective in their learning; however, the post-intervention test results were 93.5% and 89.9% from each school, the result was statistically significant (P-value 0.000) which shows that the combined-facilitation technique is a very effective teaching method. Conclusion: Despite the wide difference in the post test, which evidenced the effectiveness of the combined method, the student saw the method as not very effective, hence the need to emphasis and implement the use of the combined lecture-facilitation method to change their perception towards the teaching approach.